Christian Apologetic Theology in a West African Context - Imasogie, Osadolor (The Journal of the Interdenominational Theological Center, 1980)
To prove that a clear understanding of African traditional religion (ATR) lends itself to a fertile ground for Christian apologetics, this Nigerian author surveys the methodology of Christian apologetics. Based on the premise that if the Christian church is to seek the conversion of one whose background is ATR, it must first understand its theological roots and the theology of ATR, the author develops Christian apologetics that is informed by an understanding of ATR. God's decisive revelation in the Christ-event can legitimately be commended as the fulfillment of the longings of ATR.
free
Keywords: Africa; West – Church history; Apologetics; Theology – Africa